Employee’s Right to Rest According to Islamic Law - Ergun, Mehmet; Ergün, Mehmet (Azerbaijan Science Center, 2025)
Human beings are creatures with limited strength and energy. This characteristic of theirs is a situation that stems from their natality and nature. As a human being, a worker also gets tired after working for a while; their energy decreases, and they become completely exhausted. In order for them to regain their energy, they need to sit down and rest for a while. One of the wisdoms and reasons why Allah Almighty created nights as one of the proofs of His existence is that it is a situation and an important blessing aimed at meeting the need for rest of human beings. Because when a human being’s body gets tired, their spiritual world is also negatively affected by this situation. A person who is tired from working needs to sit down and rest for a while at certain intervals during the day in order to regain their strength and become refreshed. This right is both their human and legal right. In fact, many scientific studies show that the vast majority of work accidents and work inefficiencies are caused by employers not taking their employees’ needs for rest into consideration. In other words, the employee’s right to rest is an important right in terms of ensuring work safety and increasing work efficiency. Indeed, the principles of “no person should be given more work than they can handle”, “human beings are created as weak beings”, “do not offer your employees a job that is beyond their capacity!” are also important principles that point to the employee’s right to rest. In this full-text declaration, the issue of “Employee’s Right to Rest According to Islamic Law”, which will contribute greatly to labor and employee-employer peace, establish occupational safety and worker health, and increase work quality and production, will be examined with evidences. © 2025, Azerbaijan Science Center. All rights reserved.
İslam hüququna gör? işçinin istirah?t haqqı
Keywords: Employee; Islamic Law; Right to Rest